The hidden link between HIV and cardiomyopathy: unraveling HIV's impact on the heart - Awoyemi, Toluwalase; Tolu-Akinnawo, Oluwaremilekun Zeth; Greek, Andrew; Adenuga, Oluwakemi; Asogwa, Chukwuebuka; Ekundayo, Isaac; Odusola, Olamide; Fasehun, Oyinlola; Ajayi, Mercy; Ugoala, Onyinye; Fasehun, Luther-King; Adeleke, Oluwaseun Dorcas; et al. (Frontiers in Cardiovascular Medicine, 2025)
This comprehensive review examines the complex relationship between human immunodeficiency virus (HIV) and cardiomyopathy, focusing on the underlying molecular mechanisms, clinical manifestations, diagnostic approaches, and treatment strategies. It highlights the significant global health burden posed by HIV and its potential to cause long-term cardiovascular complications. The review investigates the pathogenesis of HIV-associated cardiomyopathy. It elucidates the intricate cellular and molecular pathways involved, including the actions of neutrophils, monocytes, macrophages, and lymphocytes in cardiac inflammation. Key signaling pathways such as TNF-NF-κB and the caspase-1 inflammasome are detailed, as they contribute to cardiac infection and injury. The clinical manifestations of HIV-associated cardiomyopathy are discussed, including fatigue, dyspnea, peripheral edema, and arrhythmias. The review outlines essential diagnostic methods, highlighting the importance of cardiac biomarkers, electrocardiography, and imaging techniques such as echocardiography and cardiac MRI. Treatment strategies are explored, encompassing lifestyle modifications, pharmacological interventions, and advanced therapies. The review underscores the importance of addressing micronutrient deficiencies, particularly selenium, in the management of HIV-associated cardiomyopathy. It also discusses the role of antiretroviral therapy and the potential benefits of intravenous immunoglobulin therapy. Furthermore, this review addresses the evolving perspective on heart transplantation for individuals with HIV. It notes that while HIV was once considered a contraindication for transplantation, recent advancements in antiretroviral therapy have led to a re-evaluation of this stance. Finally, the review identifies future research directions, emphasizing the need for biomarkers to detect at-risk patients, exploration of nutritional factors predisposing individuals to cardiomyopathy, and further investigation into advanced therapies for HIV-associated cardiomyopathy. This review significantly enhances the understanding of HIV-associated cardiomyopathy, providing valuable insights for clinicians and researchers in the fields of infectious diseases and cardiology.